2020
DOI: 10.1002/cpt.1928
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A3 and Sex Are Major Determinants of Telmisartan Pharmacokinetics—A Comprehensive Pharmacogenomic Study

Abstract: To investigate how variability in multiple pharmacokinetic genes associates with telmisartan exposure, we determined telmisartan single‐dose (40 mg) pharmacokinetics and sequenced 379 genes in 188 healthy volunteers. Intronic UGT1A variants showed the strongest associations with the area under the plasma concentration‐time curve from zero hours to infinity (AUC0–∞) and peak plasma concentration (Cmax) of telmisartan. These variants were strongly linked with the increased function UGT1A3*2 allele, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
4
12
0
Order By: Relevance
“…This variant has been linked to irinotecan toxicity in Biobank Japan [ 33 ]. According to GnomAD v2.1.1, the frequency of rs4148323-A in Europeans is only 0.2% but here we report, as seen earlier in a small sample size study [ 34 ], that the frequency in Finns is 4.2% which means an approximately 22-fold enrichment. The study concerning irinotecan-treated patients from Biobank Japan demonstrated that 51 out of the 330 subjects with normal UGT1A1 metabolism experienced adverse drug reactions (15%) whereas 8 out of 15 subjects (53%) with rs4148323-AA experienced an adverse drug reaction.…”
Section: Discussionsupporting
confidence: 69%
“…This variant has been linked to irinotecan toxicity in Biobank Japan [ 33 ]. According to GnomAD v2.1.1, the frequency of rs4148323-A in Europeans is only 0.2% but here we report, as seen earlier in a small sample size study [ 34 ], that the frequency in Finns is 4.2% which means an approximately 22-fold enrichment. The study concerning irinotecan-treated patients from Biobank Japan demonstrated that 51 out of the 330 subjects with normal UGT1A1 metabolism experienced adverse drug reactions (15%) whereas 8 out of 15 subjects (53%) with rs4148323-AA experienced an adverse drug reaction.…”
Section: Discussionsupporting
confidence: 69%
“…This variant has been linked to irinotecan toxicity in Biobank Japan 59 . According to GnomAD v2.1.1, the frequency of rs4148323-A in Europeans is only 0.2% but here we report, as seen earlier in a small sample size study 60 , that the frequency in Finns is 4.2% which means an approximately 21-fold enrichment. The study concerning irinotecan-treated patients from Biobank Japan demonstrated that 51 out of the 330 subjects with normal UGT1A1 metabolism experienced adverse drug reactions (15%) whereas 8 out of 15 subjects (53%) with rs4148323-AA experienced an adverse drug reaction.…”
Section: Discussionsupporting
confidence: 69%
“…This variant has been linked to irinotecan toxicity in Biobank Japan 59 . According to GnomAD v2.1.1, the frequency of rs4148323-A in Europeans is only 0.2% but here we report, as seen earlier in a small sample size study 60 The strength of our study is the large sample size, genotyped with a GWAS chip, which enabled us to estimate the LD structure in more detail, as compared with pharmacogenetic studies which have relied on genotyping of only a few variants. A limitation is that the sample was ascertained based on a previous diagnosis of psychosis and many patients were recruited from long-term treatment facilities and housing-units, which may skew the results towards patients who have had a sub-optimal therapeutic response, and thus divert the pharmacogenetic variant frequencies from the population mean.…”
Section: Discussionsupporting
confidence: 50%
“…A total of 379 pharmacokinetic genes ±20 kb were completely sequenced in the study participants using targeted massive parallel sequencing at the Technology Centre at Institute for Molecular Medicine Finland (Helsinki, Finland) as described previously. 19 , 20 , 21 , 22 The pharmacokinetic genes included phase I and II metabolizing enzymes, influx and efflux drug transporters, and regulatory proteins. 23 , 24 Coverage depth greater than or equal to 10×, Hardy‐Weinberg equilibrium p < 3.15 × 10 −7 (Bonferroni‐correction), and proportion missing less than or equal to 0.05 were used as quality thresholds for the sequencing data.…”
Section: Methodsmentioning
confidence: 99%